PENINGKATAN HASIL BELAJAR TEMA 4 BERBAGAI PEKERJAAN DENGAN MENGGUNAKAN METODE JIGSAW PADA SISWA KELAS IV SDN 010 SAMARINDA UTARA TAHUN PELAJARAN 2019/2020 - Agus Salim, Nur; Hermawati, Desi; Astanti, Beata (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The purpose of this class action research is to improve the learning achievement of fourth grade students, 31 people in total, at SDN 010 North Samarinda. This research was conducted in three cycles and each cycle consisted of two meetings. The student's initial data is taken from the pre cycle which was carried out before the first cycle began. Whereas, the final data is obtained at the end of each cycle after the researcher conducted the evaluation test. Student learning achievement in each cycle continues to increase from cycle I, cycle II and cycle III. Where the results obtained in Indonesian subjects in the first cycle, the average score of 72 with a completeness of 61.3%, in the second cycle, the average score of 80 with a completeness of 74% while in the third cycle, the average score of 90 with the percentage of completeness reaching 100% of 31 students. As for natural science subjects, in cycle I, the average score of 70 with a completeness percentage at 54.8%, in cycle II, the average score of 74 with a completeness of 74.2%, whereas in social studies subjects also experienced an increase in cycle I gained the average score of 69 with a percentage of 51.6% completeness, in the second cycle, the average value of 74 with a completeness of 71% and in the third cycle the average score increased to 81 with a percentage of 100% completeness. Based on the results of data analysis, the Jigsaw method can improve students learning achievement of fourth grade students of SDN 010 North Samarinda.